2020
DOI: 10.3389/fpsyg.2020.01229
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Embodiment Using 180° Stereoscopic Video

Abstract: One of the most exciting possibilities of virtual reality is inducing in participants the illusion of owning a virtual body. This has become an established methodological paradigm allowing the study of the psychological and neural correlates of various scenarios that are impossible in the real world, such as gender or age switching. Thus far, full-body ownership illusions have been implemented by using real-time body tracking and avatars based on computer-generated imagery (CGI). We propose an alternative tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Neither embodiment nor presence was examined and only 15 subjects per condition were surveyed. Landau et al (2020) showed that young adults who were embodied in a virtual body of a child using 180°stereoscopic video significantly overestimated the duration of the VR experience compared with a control group embodied in a virtual body of their own age. Furthermore, after exposing participants to a VR experience, Bansal et al (2019) observed a novel relationship between action and event speed that resulted in a recalibration of time perception in a psychophysical task.…”
Section: Time Studies In Virtual Realitymentioning
confidence: 94%
“…Neither embodiment nor presence was examined and only 15 subjects per condition were surveyed. Landau et al (2020) showed that young adults who were embodied in a virtual body of a child using 180°stereoscopic video significantly overestimated the duration of the VR experience compared with a control group embodied in a virtual body of their own age. Furthermore, after exposing participants to a VR experience, Bansal et al (2019) observed a novel relationship between action and event speed that resulted in a recalibration of time perception in a psychophysical task.…”
Section: Time Studies In Virtual Realitymentioning
confidence: 94%
“…The choice of shooting the scene from an over-the-shoulder angle was to clearly emphasize the identity of each perspective. It is technically possible to create the illusion of first-person embodiment using 360° video techniques by placing the camera at an actor’s eye level (Aitamurto et al, 2018; Landau et al, 2020). If the scene was filmed from a first-person perspective, that is, “virtually embodying” participants in the actors’ body, they would not have known whom they represent.…”
Section: Methodsmentioning
confidence: 99%
“…Communication with the world happens here, not at the meninges (as the boundaries of the brain) or an ephemeral "soul. " So close is the link to outer experience that virtual reality can, at least on the short term, trick us into illusionary body experiences (Landau et al, 2020).…”
Section: The Embodied Mind In Motionmentioning
confidence: 99%